FINANCIAL LITERACY AND ACCOUNTING LITERACY AMONG EX-MIGRANT WORKERS IN THE COMMUNITY - Amir Hamzah; Yudi Febriansyah; Teti Rahmawati; Siti Nuke Nurfatimah (ACCRUALS (Accounting Research Journal of Sutaatmadja), 2024)
The aim of this research is to examine and analyze the influence of financial attitudes and financial planning on financial literacy and accounting literacy. The methodology employed in this study is descriptive and verificative. The study population consists of ex-migrant workers in Kuningan Regency, totaling 282 individuals. Random sampling technique was used to select 133 participants. Analysis was conducted using Structural Equation Modeling (SEM), including validity and reliability tests of instruments (confirmatory factor analysis), testing the model of relationships between variables (path analysis), and forming an appropriate predictive model (structural model and regression analysis), utilizing LISREL software as the analytical tool. The research findings indicate that (1) financial attitudes do not have a significant influence on financial literacy, (2) financial planning has a positive influence on financial literacy, (3) financial attitudes have a negative influence on accounting literacy, (4) financial planning has a positive influence on accounting literacy, and (5) financial literacy has a positive influence on accounting literacy.